Environmental Awareness and Sensitivity of the Gifted Students: “Science and Art Explorers in The Nature” - (:unkn) unknown (My University, 2018)
In this study, it was aimed to investigate the effect of the six days nature education which was named TUBİTAK 4004 "Science and Art Explorers in The Nature” and was organized to improve the environmental awareness and sensitivity of the gifted students, on environmental awareness and concerns of the students. 50 seventhgrade gifted students from Istanbul, Aydin and Tekirdağ were participated in this study. The study was conducted as qualitative study and as data collection tools, two questionnaires consisting of seven open-ended questions were used to determine the environmental awareness and concerns of the students. The data was analysed by descriptive analysis method. After the activities carried out during the project period, it has been determined that the awareness and concerns of the students about the environment consciousness and the environment have improved. Students have stated that environmental education is fun, they learn a lot about the environment, living things and ecosystems together by the activities that they made and they are now more sensitive about protecting the environment.

Bu çalışmada, özel yetenekli öğrencilerin çevre farkındalık ve duyarlılıklarını geliştirmek amacıyla düzenlenen TÜBİTAK 4004 “Bilim ve Sanat Kâşifleri Doğada” adlı altı gün süren doğa eğitimi projesinin, öğrencilerin çevreye yönelik farkındalık ve duyarlılıkları üzerine olan etkisinin araştırılması amaçlanmıştır. Araştırmaya İstanbul, Aydın ve Tekirdağ illerinden 50 özel yetenekli yedinci sınıf öğrencisi katılmıştır. Nitel yöntemin kullanıldığı çalışmada, veri toplama aracı olarak öğrencilerin çevre farkındalık ve duyarlılıklarını belirlemek amacıyla yedişer açık uçlu sorudan oluşan iki anket kullanılmıştır. Veriler betimsel analiz yöntemiyle analiz edilmiştir. Proje sürecinde doğa ile ilgili yapılan etkinliklerden sonra öğrencilerin çevre bilincinin, çevreye yönelik farkındalık ve duyarlılıklarının geliştiği tespit edilmiştir. Öğrenciler çevre eğitimlerinin eğlenceli olduğunu, yapılan etkinliklerle birlikte çevre, canlılar ve ekosistem ile ilgili birçok bilgi edindiklerini, çevreyi koruma konusunda artık daha duyarlı olduklarını belirtmişlerdir.
Özel Yetenekli Öğrencilerin Çevre Farkındalık ve Duyarlılıkları: “Bilim ve Sanat Kâşifleri Doğada”
Keywords: Eğitim, Eğitim Araştırmaları; Eğitim, Özel